Landscape as metaphor: artist as metaphier - Briggs, Susan H. (Curtin University, 2002)
This research records a three year journey of exploration through the visual arts, specifically painting and drawing in relation to the landscape. The written work presented here provides a support document to my final exhibition of paintings that were exhibited in the John Curtin Gallery at Curtin University of Technology from November 24th - December 15th 2002.The writing of this exegesis is in itself a creative piece, but it is not the same as the visual research that culminates in the paintings. I am convinced that to talk about creating art actually leads one away from being in the experiencing of that art, hence this writing discusses the processes involved and not the finished work. My primary objective within this exegesis is to present a discussion centred around some of the philosophical issues that became visible whilst carrying out my practical work. This discussion is also about process itself in art making practices and research, hence this exegesis is intended to run as a parallel to the visual body of work as presented in the final exhibition of works held in the John Curtin Gallery.I have intentionally used my own practice as a device to question the choices and outcomes of art making generally in an effort to add a little colour to the larger discourse of creative practices. Some of the writing may seem personal (apart from the journal notes) and again, this is an intentional device in order to bring about a sense of embodiment within the writing itself and a way of mirroring the processes within the paintings.